Risk Assessment, Risk Management, and Risk Communication in the Carpet Industry: PT. ‘X’ Pandaan. East Jawa - Zikri Fathur Rahman1, Nur lailatul masruroh2, Abdul Rohim Tualeka1 (Indian Journal of Forensic Medicine & Toxicology, 2020)
There are many work-related accidents and diseases caused by weak risk management efforts. Risk management can be done by starting with a risk assessment. Risk assessment is an important aspect of occupational health and safety. The garment textile manufacturing industry has a high risk of occupational health and safety. This study aims to identify the level of occupational health and safety risks and provide control recommendations. This research was descriptive using the Job Safety Analysis (JSA) method. The results of the identification show that out of the 4 work stages and 19 job descriptions, 10 descriptions or 52.6% are at high risk for Occupational Safety and Health. Identified hazards include chemical, physical, ergonomic and fire hazards. High risks include hazards from chemicals as raw materials for the process of making carpets. Several control measures have been taken, but to ensure the health and safety of workers, additional efforts must be made such as personal protective equipment, special masks for use in chemical hazards and work accident emergency response procedures. Risk communication in drug companies is running well.